1980
DOI: 10.1002/ace.36719800807
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging continuing education for professionals

Abstract: Even some highly educated professionals can be hard-to-reach learners. N m and better approaches to nee& assessment and the delivery of educational services are essentkl i f real progress is to be m d .Continuing Professional Education (CPE) includes any purposeful, systematic, and sustained effort conducted by professionals after completion of their entry-level education to update or expand the proficiency, knowledge, skills, or attitudes necessary to effectively discharge their occupational roles.CPE is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…which are “perishable”. Scanlan (1980, p. 56) observed that:It is ironic that the very factors responsible for the rise of the expert represent the most potent threats to the continuity of professional proficiency. As the professional work force grows, so too does the recognition that specialized knowledge is a perishable commodity, that the skills and attitudes acquired during preparatory education are subject to rapid obsolescence, and that only by maintaining a lifelong commitment to learning can professionals expect to remain professionals and fulfil their increasingly complex obligations to their occupations, their clients and employers, and the society they serve.…”
Section: The Need For In‐service Training In Law Enforcementmentioning
confidence: 99%
See 2 more Smart Citations
“…which are “perishable”. Scanlan (1980, p. 56) observed that:It is ironic that the very factors responsible for the rise of the expert represent the most potent threats to the continuity of professional proficiency. As the professional work force grows, so too does the recognition that specialized knowledge is a perishable commodity, that the skills and attitudes acquired during preparatory education are subject to rapid obsolescence, and that only by maintaining a lifelong commitment to learning can professionals expect to remain professionals and fulfil their increasingly complex obligations to their occupations, their clients and employers, and the society they serve.…”
Section: The Need For In‐service Training In Law Enforcementmentioning
confidence: 99%
“…Scanlan (1980, p. 60) felt that some types of professionals would be harder to reach for in‐service training than others. He observed that:The present evidence suggests that hard to‐reach professionals do not constitute a homogenous group with singular characteristics, indeed, the genus “hard‐to‐reach professional” may include at least three distinct species, each with unique attributes, attributes critically important to program planners intent upon gaining their participation.…”
Section: Hard To Reach Groupsmentioning
confidence: 99%
See 1 more Smart Citation